Diagnosing the Issue: Understanding and Combating Medical Brain Drain in Bosnia and Herzegovina - Jahić, Hatidža; Hadžiahmetović-Milišić, Nejra; Dedović, Lejla; Kuloglija, Emina (Naše gospodarstvo/Our economy, 2024)
This study investigates emigration patterns among healthcare professionals in Bosnia and Herzegovina, examining the underlying reasons for emigration and proposing actionable solutions to curb this trend. A mixed-methods approach is employed, combining quantitative data from surveys administered to medical and health studies students with qualitative insights from interviews with governmental officials, language educators, and statistical agencies. The findings reveal significant dissatisfaction with socio-economic and political conditions, prompting healthcare professionals to seek opportunities abroad. Major reasons for going abroad include political instability, low wages, and poor working conditions, while better pay and career opportunities are attracting factors. While the study is limited by the lack of comprehensive official statistics on emigration, the implications of this research emphasize the need for policy interventions aiming to improve local working conditions and reform educational systems. The study provides valuable insights for policymakers and stakeholders to effectively address the issue of brain drain.